Attaining sustainable business performance via eco-innovation under ecological regulatory stringency and market turbulence. (25th March 2023) - Larbi-Siaw, Otu; Xuhua, Hu; Ofori Donkor, Derrick
Abstract: The study examines approaches wherein two external factors spur Ghanaian firms to eco-innovate: ecological regulatory stringency and market turbulence. The study's conceptual framework is evaluated using survey data from 513 Ghanaian manufacturing firms using a hybrid Partial Least Square-Structural Equation Model and Arttificial Neural Network technique, which provides support to the proposed hypothesis. Thus, by dividing eco-innovation into product eco-innovation and process eco-innovation, we infer that ecological regulation stringency improves sustainable business performance primarily through process eco-innovation instead of product eco-innovation and market turbulence has a greater impact on sustainable business performance through product eco-innovation as opposed to process eco-innovation. Our research adds to the literature on eco-innovation and green economy by providing a comprehensive framework for measuring a firm's pursuit of eco-innovation and sustainability in response to government and market pressures. We conclude by providing theoretical, methodological and practical implications. Highlights: Real effect of external pressures on eco-innovation and sustainability. Two forms of external pressures exhibit different eco-innovation promotions. Holistic framework reveals complex links between external pressures, eco-innovation, and sustainability. Use of a nascent hybrid PLS-SEM & ANN technique.